2021
DOI: 10.1017/s0967199420000805
|View full text |Cite
|
Sign up to set email alerts
|

Sperm-borne small RNAs improve the developmental competence of pre-implantation cloned embryos in rabbit

Abstract: Summary The low efficiency of somatic cell nuclear transfer (SCNT) greatly limits its application. Compared with the fertilized embryo, cloned embryos display abnormal epigenetic modification and other inferior developmental properties. In this study, small RNAs were isolated, and miR-34c and miR-125b were quantified by real-time PCR; results showed that these micro-RNAs were highly expressed in sperm. The test sample was divided into three groups: one was the fertilized group, one was the SCNT control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Sperm-borne small RNA injection of cloned bovine embryos enhanced the developmental competence and significantly increased the live birth rate and decreased the birth weights of offspring [152]. Similarly, the injection of sperm small RNA into cloned rabbit embryos increased the total cell number and H3K9me3 level as well as decreased the apoptosis index of cloned rabbit blastocysts [153].…”
Section: The Use Of Non-chemical and Biological Agents As Epigenetic ...mentioning
confidence: 93%
“…Sperm-borne small RNA injection of cloned bovine embryos enhanced the developmental competence and significantly increased the live birth rate and decreased the birth weights of offspring [152]. Similarly, the injection of sperm small RNA into cloned rabbit embryos increased the total cell number and H3K9me3 level as well as decreased the apoptosis index of cloned rabbit blastocysts [153].…”
Section: The Use Of Non-chemical and Biological Agents As Epigenetic ...mentioning
confidence: 93%
“…SCNT was carried out as previously reported [14]. Three drops of micromanipulation M2 medium containing 7.5 μg/ml cytochalasin B and 10% FBS and one drop of 5% PVP (Sigma–Aldrich) were put into a 35 mm dish (Corning, NY, USA) and covered with mineral oil (Sigma–Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…The role of sperm-borne miR-34c in the first cleavage division of murine embryos remains unclear [ 8 , 20 ], but an increasing number of studies have shown that miR-34c participates in early embryonic development. For example, in rabbits and cows, miR-34c improves the developmental competence of embryos generated by somatic cell nuclear transfer (SCNT) [ 10 , 21 ]. In addition, we have demonstrated that spermatozoan miR-34c levels are correlated with intracytoplasmic sperm injection (ICSI) outcomes, such as embryo quality and clinical pregnancy and live birth rates [ 11 ].…”
Section: Introductionmentioning
confidence: 99%